Optimizing airway network efficiency with the A-star algorithm: a case study of Ho Chi Minh FIR - Ngoc Hoang Quan Nguyen; Thi Hoai An Vu; Hoang Mai Le; Mai Phuong Nguyen; Thi Thu Tra Le; Thi Thuy Trang Nguyen; Ngoc Nhu Y Nguyen (Aviation)
Airway network optimization is crucial for airspace planning, addressing high traffic density and alleviating pressure on Air Traffic Controllers. With the rapid growth of civil aviation, overloaded airways and congestion have become significant challenges. Vietnam’s air transport sector plays a vital role in economic and social development, enhancing connectivity across the Asia-Pacific region. Additionally, Vietnam has led the global recovery of domestic aviation post-COVID-19 and, as the world’s fifth fastest-growing aviation market, is expected to reach 150 million air transport passengers by 2035. This highlights Vietnam’s dynamic growth and strategic importance within global aviation. However, this rapid expansion has exposed vulnerabilities in Vietnam’s airways, particularly within the Ho Chi Minh Flight Information Region (HCM FIR), where congestion and overload are evident, especially during adverse weather. To address these challenges, this study proposes optimizing the airway network in 2D space using the A-star algorithm, tailored for the HCM FIR. This approach aims to reduce flight distances, improve operational efficiency, and ease ATC workloads, marking a critical step toward enhancing Vietnam’s airspace management system.